Cooperation, comity, and competition policy - Guzman, Andrew T. (New York ; Oxford : Oxford University Press, 2011)
'Cooperation, Comity, and Competition Policy' edited by Andrew T. Guzman, illustrates how domestic competition law policies intersect with the realities of international business.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Conflict of laws -- Antitrust law; Antitrust law -- International cooperation; Antitrust law (International law)